Preparation and properties of poly(ethylene terephthalate)/nanoclay nanocomposites fibers - Hojiyev, Rustam; Altun, Şule; Ulcay, Yusuf (Fiber Society, 2012)
Preparation and properties of poly(ethylene terephthalate)/nanoclay nanocomposites fibers
Keywords: Polyethylene Terephthalates; Mechanical Properties; Extruders